Pd/C-Catalyzed Homocoupling Reaction for the Synthesis of Symmetrical Biaryl Diamides - Shen, Guodong; Wang, Yichen; Zhao, Xiliang; Huangfu, Xinlei; Tian, Yanmeng; Zhang, Tongxin; Yang, Bingchuan (Synlett, 2017)
Pd/C was found to be an efficient and convenient metal catalyst in the homocoupling reaction for the synthesis of symmetrical biaryl diamides. The catalyst system Pd/C–KOAc showed high catalytic activity, and a variety of symmetrical biaryl diamides were conveniently synthesized from 2-halo-N-phenylbenzamides in moderate to good yields.
Keywords: Pd/C; homocoupling reaction; symmetrical biaryl diamides; 2-halo-N-phenylbenzamides; recyclability